"Fact-Checking Africa": Epistemologies, data and the expansion of journalistic discourse. Issue 8 (14th September 2018) - Cheruiyot, David; Ferrer-Conill, Raul
Abstract : The prominence of "fake news" today has sparked an open challenge to the legitimacy of traditional news media. As a result, a series of independent data-driven organisations are emerging to fact-check legacy news media as well as other news sources. This study examines how these actors advocate and adopt journalistic practice and the perceived impact they have on news journalism. We draw our data from in-depth interviews with 14 practitioners working in three organisations—Code for Africa, Open Up and Africa Check—that are currently leading major data and fact-checking operations in sub-Saharan Africa. Our findings show that while these non-journalistic actors are at the periphery of news media as institutions, their operations, activities and goals are at the heart of journalistic discourse. In their data strategies, they emerge as data advocates and activists seeking to reformulate fact-checking processes within news media.